# Thus when p is an integer bessels equation has a

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: )2 an xn+r + n=2 p2 an xn+r = 0. n=0 This simpliﬁes to yield ∞ ∞ [(n + r)2 − p2 ]an xn+r + n=0 an−2 xn+r = 0, n=2 or after division by xr , ∞ ∞ [(n + r)2 − p2 ]an xn + n=0 an−2 xn = 0. n=2 23 Thus we ﬁnd that ∞ (r2 − p2 )a0 + [(r + 1)2 − p2 ]a1 x + {[(n + r)2 − p2 ]an + an−2 }xn = 0. n=2 The coeﬃcient of each power of x must be zero, so (r2 − p2 )a0 = 0, [(r +1)2 − p2 ]a1 = 0, [(n + r)2 − p2 ]an + an−2 = 0 for n ≥ 2. Since we want a0 to be nonzero, r must satisfy the indicial equation (r2 − p2 ) = 0, which implies that r = ±p. Let us assume without loss of generality that p ≥ 0 and take r = p. Then [(p + 1)2 − p2 ]a1 = 0 ⇒ ⇒ (2p + 1)a1 = 0 a1 = 0. Finally, [(n + p)2 − p2 ]an + an−2 = 0 ⇒ [n2 + 2np]an + an−2 = 0, which yields the recursion formula an = − 1 an−2 . 2np + n2 (1.21) The recursion formula implies that an = 0 if n is odd. In the special case where p is a nonnegative integer, we will get a genuine power series solution to Bessel’s equ...
View Full Document

## This document was uploaded on 01/12/2014.

Ask a homework question - tutors are online